FTA AND FMECA ANALYSIS FOR DETERMINE CRITICAL COMPONENTS OF DIESEL GENERATOR CUMMINS KTA 38D - Wakijo Wakijo; Joko Purnomo; Rakhmad Susilo (Indonesian Naval Technology College STTAL, 2022)
A diesel Generator is equipment has functions as a power generator and electricity supply. Tanker warship is oneof the navy warships applying diesel generator Cummins KTA 38D for electricity supply when going on missionarea or at basecamp. On diesel generator system consists of 7 (seven) sub-system are coolant sub-system,seawater cooling sub-system, fuel oil sub-system, air intake and exhaust sub-system, Lub oil sub-system, Electricstarter sub-system and controlling sub-system. Due high operating hours, the potential for damage is increasing,because damage a component diesel generator. According ship damage report data, the percentage damage ofdiesel generator reach until 38.5% from total equipment damage that occurred during 2016-2022 year. Based onthat phenomena, this research will identifcation factors that cause damage and determine the components havehigh criticality in the diesel generator using the FTA (Fault Tree Analysis) to systematically explain unexpectedcausal factors that lead to failure, and the FMECA (Failure Mode Effect And Criticality Analysis) method to identifycritical components according factors have the highest critical point with calculation of the Risk Priority Number(RPN). The results of calculations and analysis using the FTA and FMECA methods, there are 6 (six) criticalcomponents with the highest RPN value in the diesel generator system, that Tube sea water component (375,4)with the risk of leaking, Impeller components (377,1) with a risk of corrosion/crack, Body Cover SW (372,0) witha risk of corrosion, Mechanical Seals (369,8) with a risk of leaking/damage, strainer (369,1) component with a riskof corrosion, Rectangular seal HE (367,9) a risk leakage and Battery (371,0) with a risk no power electric for startengine.Keywords: Diesel generator, FTA, FMECA, Critical components